Identification of Technical Requirement for Improving Quality of Local Online Food Delivery Service in Yogyakarta - Cecilia Desvita Ratna Elvandari; Anggoro Cahyo Sukartiko; Arita Dewi Nugrahini (Universitas Padjadjaran, 2017)
Increased internet usage and fast-paced consumer’s demands have created business opportunities, including online food delivery services. However, competition with similar national-scale businesses allegedly contributed to the decline in the number of XYZ company orders, one of the food-delivery service providers in Yogyakarta. Therefore, this study aimed to identify the need’s attributes of the daring food delivery service consumers, to find out the service-quality satisfaction level, and to determine the technical requirement for improving the delivery service. The combination of Servqual and Quality Function Deployment (QFD) were then used to reach the research goals. The online survey instruments, which were borrowed from the previous studies and adapted for this study, were distributed from June 2016 to February 2017 to more than 700 XYZ’s consumers, with the number of respondents who answered as many as 213 peoples. Cronbach’s Alpha, the most common test for multiple Likert questions in a survey, was then used for analyzing the collected data. The result shows that order conformity; politeness and friendliness of messengers and administrative workers; cleanliness of food box; a good conditionof received ordered food; and affordable delivery costs are the top five attributes of consumer needs. Meanwhile, the top five observed technical requirements are the provision of skills training to messengers and administrative workers; periodic evaluations of service performance; the regular addition of food outlet members; providing map feature on the company website, and provision of ordering applications. The identified requirements can benefit local food delivery service providers in competing with national scale competitors and adapt to disruptive age.